Validation of an instrument for understanding school absence: the Swedish version of the adapted school refusal assessment scale-revised - Strömbeck, Johan; Heyne, David; Ferrer-Wreder, Laura; Alanko, Katarina (Springer Science and Business Media LLC, 2025)
Background
The School Refusal Assessment Scale-Revised (SRAS-R) is a widely used measure to understand school attendance problems. However, previous evaluations have yielded inconsistent findings on the factor structure.
Methods
We prepared a Swedish translation of the original SRAS-R plus the eight alternative items in the adapted versions of the SRAS-R (i.e., the A-SRAS-R). Subsequently, we tested the Swedish A-SRAS-R in a pilot testing, evaluated its factor structure, internal consistency, convergent and discriminant validity, and compared the model fit and internal consistency with the SRAS-R. Participants were students (n = 399) aged 12–16 years (M = 14.7, SD = 0.9) and their parents (n = 251).
Results
Results supported a four-factor solution of the A-SRAS-R. However, the fourth factor was non-optimal concerning factor loadings and reliability. We found consistent evidence of convergent validity, and inconsistent evidence of discriminant validity.
Conclusion
The results provide support for the A-SRAS-R being psychometrically sound, and superior in comparison to the SRAS-R. Notwithstanding the need for further development of the fourth factor, the A-SRAS-R appears to be a valuable instrument for understanding school absence among Swedish young people.